2015
DOI: 10.1002/stem.2077
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Enhancement of Cell Proliferation in the Postnatal Neurogenic Niche of the Mammalian Spinal Cord

Abstract: The region surrounding the central canal (CC) of the spinal cord is a highly plastic area, defined as a postnatal neurogenic niche. Within this region are ependymal cells that can proliferate and differentiate to form new astrocytes and oligodendrocytes following injury and cerebrospinal fluid contacting cells (CSFcCs). The specific environmental conditions, including the modulation by neurotransmitters that influence these cells and their ability to proliferate, are unknown. Here, we show that acetylcholine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 45 publications
2
22
0
1
Order By: Relevance
“…Previous work has shown that embryonic spinal cord stem cells and adult ependymal cells give rise to different proportions of neural cell types (Kalyani et al, 1997, Barnabe-Heider et al, 2010), our data support that further therapies should focus on the recruitment of ependymal cells and their differentiation to oligodendrocyte rather than into neurons to increase functional recovery. Previous studies showed that exogenous growth factors can modulate oligodendrocyte proliferation and suggested that this would be a beneficial target for further drug discovery and therapies for SCI (Corns et al, 2015). Our data agrees with this argument and further indicates that modulating stem cell differentiation towards the oligodendrocyte lineage will be influenced by age-dependent differences in intrinsic stem cell potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that embryonic spinal cord stem cells and adult ependymal cells give rise to different proportions of neural cell types (Kalyani et al, 1997, Barnabe-Heider et al, 2010), our data support that further therapies should focus on the recruitment of ependymal cells and their differentiation to oligodendrocyte rather than into neurons to increase functional recovery. Previous studies showed that exogenous growth factors can modulate oligodendrocyte proliferation and suggested that this would be a beneficial target for further drug discovery and therapies for SCI (Corns et al, 2015). Our data agrees with this argument and further indicates that modulating stem cell differentiation towards the oligodendrocyte lineage will be influenced by age-dependent differences in intrinsic stem cell potential.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that neurotransmitters influence neurogenesis both during embryonic development and in the adult brain and spinal cord in several species, e.g. in mammals, salamanders and zebrafish 21 22 23 24 . The role of dopamine signalling in neurogenesis in the mammalian brain was addressed in different experimental settings, which collectively indicated region- and cell-type specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…resorption of cilia [39]) in this cellular compartment with major functional consequences. Interestingly, it has been recently demonstrated that signalling via nicotinic acetylcholine receptors modulates cell proliferation of ependymal cells in the spinal cord [40], highlighting the importance of neurotransmitter regulation of progenitor cell behaviour.…”
Section: Camentioning
confidence: 99%